2006
DOI: 10.1007/bf03327746
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic monitoring of restricted eating disorders by indirect calorimetry: a useful cognitive approach

Abstract: Indirect calorimetry represents a useful approach for determining REE and prescribing diets in these patients. Moreover, the combined use of anthropometric techniques allows to accurately assess and adjust therapy according to the patient's progress. This study shows that restricted eating disorders are characterized by a recovery of FFM related to improvement of body weight and REE/day. On the contrary, the increase of AFA revealed a recovery of fat-metabolism (corresponding to RQ decrease) and lipid/carbohyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Our results suggest that there are no significant differences in REE, either crude or adjusted for LBM, between RAN and C women. Previous studies have reported that REE increases from AN to the refeeding period, 8,12,13,29,[57][58][59][60] as would be expected given that as refeeding and weight restoration occur, both LBM and FM increase, resulting in concomitant changes in REE. Yet, following weight restoration, REE has been found to be lower or similar to control participants.…”
Section: Discussionmentioning
confidence: 69%
“…Our results suggest that there are no significant differences in REE, either crude or adjusted for LBM, between RAN and C women. Previous studies have reported that REE increases from AN to the refeeding period, 8,12,13,29,[57][58][59][60] as would be expected given that as refeeding and weight restoration occur, both LBM and FM increase, resulting in concomitant changes in REE. Yet, following weight restoration, REE has been found to be lower or similar to control participants.…”
Section: Discussionmentioning
confidence: 69%
“…The nutritional programme was personalized and the therapeutic contract foresaw in the energy balance decrease in order to increase the percentage of FFM to improve the RQ value. The patients were encouraged to eat three meals per day and one or two snacks per day, corresponding to the value of TEE calculated [REE measured by indirect calorimetry plus PAL (physical activity level), after removing approximately 500 kcal/day] [12]: 50-60% of the energy derived from carbohydrates, 25-30% from fat and 15-20% from proteins, according to LARN [13]. The dietary programme was re-evaluated during long-term treatment at regular interval time (every 6 months), on the basis of personal needs, i.e.…”
Section: Resting Energy Expenditurementioning
confidence: 99%
“…Indirect calorimetry is a non-invasive and low-cost method used to determine the basal metabolic rate that provides information to raise an adequate nutritional intervention and monitoring eating disorder patients (Dragani et al, 2006;Hlynsky et al, 2005;Scalfi et al, 2010;Schebendach et al, 1995).…”
Section: Indirect Calorimetrymentioning
confidence: 99%
“…Furthermore the additional use of anthropometric measurements allows the adaption of the nutritional therapy to the patient's evolution (Dragani et al, 2006).…”
Section: Indirect Calorimetrymentioning
confidence: 99%